Point of Care Diagnostic Devices for Rapid Detection of Novel Coronavirus (SARS-nCoV19) Pandemic: A Review - Koteswara Rao, Vamkudoth (Frontiers in Nanotechnology, 2021)
Coronaviruses are recognized as causative agents of human diseases worldwide. In Wuhan, China, an outbreak of Severe acute respiratory syndrome novel Coronavirus (SARS-nCoV-2) was reported at the end of December 2019, causing 63 million COVID cases and 1.3 million deaths globally by 2 December, 2020. The transmission risk forecasts and the SARS-nCoV-2 epidemic pattern are progressive. Unfortunately, there is no specific FDA approved drugs or vaccines available currently to treat SARS-nCoV-2. In response to nCoV-2 spread, the rapid detection is crucial for estimating the severity of the disease and treatment of patients. Currently, there are several RT-PCR based diagnostic kits available for SARS-nCoV-2 detection, which are time-consuming, expensive, need advanced equipment facilities and trained personnel. The cost of diagnosis and the unavailability of sufficient test kits may prevent to check community transmission. Furthermore, expanding the testing facilities in asymptomatic cases in hotspots require more Point of Care (PoC) devices. Therefore, fast, inexpensive, and reliable methods of detection of SARS-nCoV-2 virus infection in humans is urgently required. The rapid and easy-to-use devices will facilitate onsite testing. In this review, nucleic acid assays, serological assays, multiplex assays, and PoC devices are discussed to understand various diagnostic approaches to reduce the spread and mortality rate in the future. Aptamer based detection is most specific, inexpensive and rapid detection of SARS-nCoV-2 without laboratory tools. To the best of our knowledge more than 900 SARS-nCoV-2 test kits are in pipeline, among 395 test kits are molecular bested test kits and only few test kits are developed using Aptamer technology.